Etika Digital dan Kepentingan Bersama: Analisis Bonum Commune Thomas Aquinas di Era Disrupsi Digital (Pusat Riset dan Inovasi Nasional, 2026)
This article discusses the relevance of the concept of the bonum commune (the common good) in the thought of Thomas Aquinas as a moral foundation in the era of digital disruption. The era of digital disruption is characterised by profound changes in the way humans live, interact, and utilise technology. Amidst these developments, a weak moral foundation has led to a lack of technological orientation towards the common good. Without a fundamental moral foundation, technology will be directed solely towards profitability, disregarding human values and fostering an individualistic society. This study employs a qualitative method based on a literature review, analysed through a hermeneutic reading of Aquinas’s principal work, the *Summa Theologica*, as well as literature on digital ethics. The results of the study indicate that the bonum commune is a fundamental ethical principle that can guide the use of digital technology towards justice, social responsibility, and the common good.